Looking At the Past and Heading to the Future: Meeting Summary of the 6th European Workshop on Plant Chromatin 2019 in Cologne, Germany - Moreno-Romero, Jordi; Probst, Aline V.; Trindade, Inês; Kalyanikrishna,; Engelhorn, Julia; Farrona, Sara (Frontiers in Plant Science, 2020)
In June 2019 more than hundred plant researchers met in Cologne, Germany, for the 6th European Workshop on Plant Chromatin (EWPC). This conference brought together a highly dynamic community of researchers with the common aim to understand how chromatin organization controls gene expression, development and plant responses to the environment. New evidence showing how epigenetic states are set, perpetuated and inherited were presented and novel data related to the three-dimensional organisation of chromatin within the nucleus were discussed. At the level of the nucleosome, its composition by different histone variants and their specialized histone deposition complexes were addressed as well as the mechanisms involved in histone post-translational modifications and their role in gene expression. The keynote lecture on plant DNA methylation by Julie Law (SALK Institute) and the tribute session to Lars Hennig, honoring the memory of one of the founders of the EWPC who contributed to promote the plant chromatin and epigenetic field in Europe, added a very special note to this gathering. In this perspective article we summarize some of the most outstanding data and advances on plant chromatin research presented at this workshop.